CORRECTION OF THE FUNCTIONAL STATE OF THE OPERATED LIMB IN ELDERLY PATIENTS WITH THE CONSEQUENCES OF TOTAL HIP ARTHROPLASTY AND OBESITY USING PHYSICAL THERAPY - Partsey, O. S.; Tsyhanovska, N. V.; Skalski, D. W. (Rehabilitation and Recreation, 2025)
Purpose: to assess the effectiveness of the developed physical therapy program for elderly patients with the consequences of total hip arthroplasty and obesity in the long-term after endoprosthetics on the dynamics of the functional ability of the hip joint and motor capabilities during walking. Material. During the study, 99 elderly people were examined. The control group consisted of 34 people who had no history of total lower limb arthroplasty and were of normal body weight. The comparison group consisted of 33 people who had undergone total hip arthroplasty and were of normal body weight. The main group consisted of 32 people who had undergone arthroplasty and were obese. A three-month physical therapy program was developed and implemented for them, using therapeutic exercises on the Redcord NEURAC suspension system to improve strength, flexibility, gait training, balance exercises on BOSU platforms, massage of the operated lower limb, Proprioceptive Neuromuscular Facilitation, and an educational component (diet modification). The effectiveness was assessed by the results of the visual analogue pain scale, Modified Harris Hip Score, Forgotten Joint Score-12, Functional Gait Assessment. Results. Elderly patients with consequences of total hip arthroplasty and obesity were found to have a deterioration in the functioning of the hip joints in the form of pain syndrome (according to the visual analogue scale), deterioration in the functional activity of the operated limb and difficulties in performing activities of daily living (according to the Modified Harris Hip Score, Forgotten Joint Score-12), and disturbances during various types of gait (according to the Functional Gait Assessment). The studied functional capabilities of elderly patients with hip joint endoprosthesis and obesity in the long-term period of endoprosthesis (more than 1 year) were worse (p<0.05) compared to a similar contingent of patients, but with normal body weight. The approved comprehensive physical therapy program revealed an improvement in the patients' condition due to the impact on the components of hip joint dysfunction by reducing pain, expanding motor functional capabilities when performing various activities compared to baseline indicators for all studied parameters (p<0.05). Conclusions. Physical therapy is advisable to prescribe for the comprehensive correction of signs of motor dysfunction of the operated limb and improving gait in elderly patients with hip joint endoprosthesis and obesity.